Combination strategies to enhance antitumor ADCC. (May 2012) - Kohrt, Holbrook E; Houot, Roch; Marabelle, Aurélien; Cho, Hearn Jay; Osman, Keren; Goldstein, Matthew; Levy, Ronald; Brody, Joshua
The clinical efficacy of monoclonal antibodies as cancer therapeutics is largely dependent upon their ability to target the tumor and induce a functional antitumor immune response. This two-step process of ADCC utilizes the response of innate immune cells to provide antitumor cytotoxicity triggered by the interaction of the Fc portion of the antibody with the Fc receptor on the immune cell. Immunotherapeutics that target NK cells, γδ T cells, macrophages and dendritic cells can, by augmenting the function of the immune response, enhance the antitumor activity of the antibodies. Advantages of such combination strategies include: the application to multiple existing antibodies (even across multiple diseases), the feasibility (from a regulatory perspective) of combining with previously approved agents and the assurance (to physicians and trial participants) that one of the ingredients – the antitumor antibody – has proven efficacy on its own. Here we discuss current strategies, including biologic rationale and clinical results, which enhance ADCC in the following ways: strategies that increase total target–monoclonal antibody–effector binding, strategies that trigger effector cell 'activating' signals and strategies that block effector cell 'inhibitory' signals.